PERBEDAAN EFEKTIVITAS PELARUT ORANGE OIL TERHADAP SEALER BERBASIS RESIS DAN ZINC OXIDE EUGENOL - Haryotejo, Eric Alexander (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
This study aims to determine the differences in the effectiveness of orange oil solvent against resin-based sealers and zinc oxide eugenol. The samples of this study were resin based sealers and zinc oxide eugenol based sealers which were molded in a cylindrical mold made of aluminum with a diameter of 10 mm and a height of 3 mm. The total sample size in this study was 60 samples, then divided into 4 groups, 2 groups for resin-based sealers with a time of 2 minutes and 5 minutes, and a sealer based on zinc oxide eugenol with a time of 2 minutes and a time of 5 minutes, after which it was put into incubator with a temperature of 370C for 48 hours, then weighed for each group. Data analysis used paired T test with the Kolmogorov Smirnov normality test. The results showed that the orange oil solvent did not have a significant difference to the resin-based sealers and the zinc oxide eugenol-based sealers. At the immersion time of 2 minutes, the solubility of resin-based sealers and zinc oxide eugenol did not have significant differences (p> 0.05). Based on the research results, it can be concluded that orange oil solvent is equally effective in both sealers, neither is more effective than the other Keywords: Orange Oil solvent, resin sealer, Zinc Oxide Eugenol sealer.